Pentingnya Pendidikan Kewarganegaraan (PKn) Sebagai Tiang Hak Asasi Manusia di Papua - Ode Jamal; Marthen Timisela (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2021)
Civic education is a crucial element in realizing responsible citizenship. In Papua, where there is cultural diversity and complex socio-political challenges, the development of human rights is often hampered. In this context, civic education serves as a foundation that can strengthen understanding and respect for human rights. This article aims to examine the significance of civic education in Papua, emphasizing its impact on human rights awareness and community participation. The research applies a qualitative approach to collect data from various sources, including interviews with educators and human rights activists, as well as document analysis of relevant education policies in Papua.